Makna dan Perilaku Jihad GP Ansor Tegalwangi: Analisis Sosiologi Pengetahuan - Imam Muhajir Dwi Putra (Jurnal Pemikiran Islam, 2022)
This article aims to reveal the meaning of jihad from the view of GP Ansor Tegalwangi and its relation to knowledge and social construction. This article uses a qualitative approach, in which the researcher presents data in a descriptive-analytical form. This study concludes that there are three meanings of jihad from the perspective of GP Ansor Tegalwangi. First, the objective meaning is cultural-institutional jihad resulting from the process of appreciating the verses of the Qur’an by individuals, which then becomes collective knowledge. Second, the expressive meaning can be seen from the individual's perception of the experience of jihad in the organizational sphere. Third, the meaning of the documentary is in the form of an action performed that then became a tradition as a whole. Thus, jihad is not only oriented towards status quo political goals, but jihad is also a concept that leads individuals to a priori knowledge; the meaning of the concept of jihad strongly influences the externalization of jihad. The meaning and implementation of jihad also cannot be separated from the context of society, including its sociological and humanitarian aspects.AbstrakArtikel ini bertujuan mengungkap makna jihad dari pandangan GP Ansor Tegalwangi dan kaitannya dengan pengetahuan dan konstruksi sosial. Artikel ini menggunakan pendekatan kualitatif, di mana peneliti menyajikan data dalam bentuk deskriptif-analitik. Kajian ini menyimpulkan bahwa ada tiga makna jihad dari sudut pandang GP Ansor Tegalwangi. Pertama, makna objektif adalah jihad kultural-institusional yang dihasilkan dari proses penghayatan ayat-ayat Al-Qur'an oleh individu, yang kemudian menjadi pengetahuan kolektif. Kedua, makna ekspresif dapat dilihat dari persepsi individu terhadap pengalaman jihad dalam lingkup organisasi. Ketiga, makna dokumenter berupa aksi yang dilakukan yang kemudian menjadi tradisi secara keseluruhan. Dengan demikian, jihad tidak hanya berorientasi pada tujuan politik status quo, tetapi jihad juga merupakan konsep yang membawa individu pada pengetahuan apriori; pemaknaan konsep jihad sangat mempengaruhi eksternalisasi jihad. Makna dan implementasi jihad juga tidak lepas dari konteks masyarakat, termasuk aspek sosiologis dan kemanusiaan.